Functional and Radiological Outcome of Displaced Lateral End Clavicle Fractures Treated With Open Reduction and Endobutton Fixation - Sree Shangamithra; Prem Kumar Kothimbakkam; Sanjay Nallagounder Krishnasamy; Thirumal Ranganathan; Bharath Vadivel Kumar; Vijayashankar Murugesan (Journal of Orthopaedic Case Reports)
Introduction: Displaced lateral end clavicle fractures are challenging injuries with a high risk of non-union and functional impairment when treated conservatively. Open reduction and endobutton fixation is a novel surgical technique that aims to provide stable fixation while preserving shoulder biomechanics, potentially improving functional and radiological outcomes compared to traditional methods. Materials and Methods: This prospective study included 20 male patients (mean age: 35.2 years, range: 18–56) with displaced lateral clavicle fractures (Neer type IIB and type V). All patients underwent open reduction and fixation using a twin coracoclavicular endobutton construct. Functional outcomes were assessed using the Constant-Murley scores at 6 weeks, 3 months, 6 months, and 12 months. Radiological outcomes, including fracture union and residual displacement, were evaluated with serial radiographs. Complications, return to activity, and patient satisfaction were also analyzed. Results: The mean Constant-Murley score improved significantly from 60.3 ± 8.1 at 6 weeks to 87.4 ± 4.8 at 6 months (P < 0.01), stabilizing at 88.1 ± 5.2 by 12 months. Union was achieved in 95% of cases by 6 months, with a mean residual displacement of 1.1 mm. Complications were minimal (5% each for superficial infection and mild stiffness). All patients returned to sedentary work within 8 weeks and full manual labor or sports by 6 months. Patient satisfaction was high, with 90% reporting being “highly satisfied” at the end of 1 year. Conclusion: Open reduction and endobutton fixation for displaced lateral clavicle fractures provide excellent functional recovery, high union rates, and minimal complications. This technique offers a reliable alternative to traditional fixation methods, particularly for young and active individuals. Further comparative studies and long-term follow-up are warranted to establish its role as the gold standard.